Faktor yang Berhubungan dengan Pola Pengelompokkan Kasus Demam Berdarah Dengue (DBD) di Temanggung, Jawa Tengah - Nur Alvira Pascawati; Sahid Sahid; Sukismanto Sukismanto; Hesti Yuningrum (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Dengue Hemorrhagic Fever (DHF) in Central Java Province is in the second position after East Java-based on mortality rates and Temanggung District is one of the areas in Central Java, which is in high endemic status. The level of dependence of DHF in an area can be influenced by DHF in other adjacent areas. The spread of this disease through mosquito bites from one place to another depends on the presence of the cases and the vector of Aedes sp. This study aimed to identify factors related to the clustering pattern of DHF cases in Temanggung, Central Java. This study used a cross-sectional design and was carried out in the Kandangan Health Center Work Area, Temanggung District. The sample of this study was the houses of all DHF cases in 2020 as many as 60 houses with the research variables: the existence of Aedes sp., vector breeding sites, population density, and time of occurrence. This study uses clustering analysis in the form of the Average Nearest Neighbor (ANN) test with =0.05. The results showed that the factors related to the case-grouping pattern in the Kandangan Health Center Work Area were the presence of Aedes sp., vector breeding sites, high population density, and peak dengue cases that occurred in January and February. The results of this study can be used to determine priority areas in controlling dengue cases in an area.